Luteinizing hormone supplementation in women with hypogonadotropic hypogonadism seeking fertility care: Insights from a narrative review - Di Segni, Noemi; Busnelli, Andrea; Secchi, Matteo; Cirillo, Federico; Levi-Setti, Paolo Emanuele (Frontiers in Endocrinology, 2022)
The management of infertile women affected by hypogonadotropic hypogonadism (HH) or conditions mimicking it is particularly challenging. In the present narrative review, we aimed to synthesize the available evidence on the benefit (if any) of exogenous luteinizing hormone (LH) supplementation in this group of patients. Available data support LH supplementation in women with organic or functional HH. On the contrary, the benefit of exogenous LH on reproductive outcomes both in advanced maternal age patients and in cases of depletion of FSH and LH levels induced by GnRH analogues has not been demonstrated. unfortunately, the inhomogeneous study populations as well as the methodological heterogeneity between studies focused on women affected by conditions mimicking HH do not allow reliable conclusions to be drawn. .